Ocorrência do gênero Dolyobius Linnavuori (Hemiptera, Cicadellidae) no Brasil e descrição domacho de Dolyobius distinctus Linnavuori - ZANOL, KETI MARIA ROCHA (Acta Biológica Paranaense, 2004)
O macho de Dolyobius distinctus Linnavuori, 1959 é descrito, sendo a primeira ocorrência do gênero no Brasil. ABSTRACT The male of Dolyobius distinctus Linnavuori, 1959 is described and this genus is reported for the first time in Brazil. RÉSUMÉ Le mâle de Dolyobius distinctus Linnavuori, 1959 est décrit et ce genre est rapporté pour la première fois au Brésil.